Early appearance and possible functions of non-neuromuscular cholinesterase activities - Falugi, Carla (Frontiers in Molecular Neuroscience, 2012)
The biological function of the cholinesterase (ChE) enzymes is well known and has been studied since the beginning of the XXth century; in particular, acetylcholinesterase (AChE, E.C. 3.1.1.7) is an enzyme playing a key role in the modulation of neuromuscular impulse transmission. However, in the past decades, there has been increasing interest concerning its role in regulating non-neuromuscular cell-to-cell interactions mediated by intracellular ion concentration changes, like the ones occurring during gamete interaction and embryonic development. An understanding of the mechanisms of the cholinergic regulation of these events can help us foresee the possible impact on environmental and human health, including gamete efficiency and possible teratogenic effects on different models, and help elucidate the extent to which exposure to ChE inhibitors may affect human health.